TAFSIR AYAT PERNIKAHAN PERSPEKTIF K.H. MUHAMMAD HASYIM ASY’ARI - Habibi Al Amin (LPPM UNHASY, 2023)
This Paper aims to describe living Qur’an of Tebuireng Santri Jombang, Jawa Timur Indonesia who have married. This research confirms the presumption that the stronger santri identity, the more obvious the style of santri’s ideology. This research measures santri’s behavior by using KH. Hasyim Asy'ari's concept of marriage, Ḍaw' al-miṣbaḥ fῙ bayani aḥkam al-nikaḥ. The location is Pondok Pesantren Tebuireng, Jombang. Data were collected through interviews and observations. This study concludes that santris Tebuireng, Jombang dominantly follow KH. Hasyim Asy’ari’ exegesis in Quran verses mariage, including marriage practices and household conflict handling. Keywords: living Quran, exegesis, Quran mariage Verses , KH. Hasyim Asy’ari, santri tebuiureng. DAFTAR PUSTAKA Departemen Agama, 2007. al-Quran dan Terjemahannya, Jakarta: Dirjen Bimbingan Masyarakat Islam. Abi Abdillah Muhammad bin zain al-Qazwani, Sunan ibnu Majjah, Beirut: Dar al-Fikr. Abi Yahya Zakariya, Fath al-Wahhb, Kitab an-Nikāh, Jakarta: al-Haramain Jaya Indonesia. Asy’ari, Muhammad Hasyim, Ḍaw al-Miṣbāḥ fī Bayāni Aḥkām an-Nikāḥ, Jombang: Maktabah al-Turats al-Islamy. __________ at-Tibyān fi Nahy an-Muqhathan’ati al-Arhām wa al-Qarib wa al-Ikhwān , Jombang: Maktabah al-Turats al-Islamy. Ali bin Umar abul Hasan ad-Daruqutni al-Baghdadi, 1996. Sunan Daruqutni, Bairut: Ma’rifah. Al-Bantani, Muhammad bin ‘Amr bin Ali Nawawi. Syarah ‘Uqud al-Lujjain fi Bayan Huquq al-Zaujain, Beirut: Dar al-Kutub al-Ilmiah. al-Haitami Ibnu Hajar, Tuhfatul Muhtaj fi Syarh al-Minhaj, Bairut: Daru Ihya’ at Turats al- ‘Arabi. Al Amin, Habibi.